Analysis of time-resolved wind-driven rain on an array of low-rise cubic buildings using large eddy simulation and an Eulerian multiphase model. (March 2017) - Kubilay, A.; Derome, D.; Carmeliet, J.
Abstract: Time-resolved wind-driven rain (WDR) load is investigated on an array of low-rise cubic buildings using an Eulerian multiphase (EM) model together with large eddy simulation (LES). The influence of wind-flow unsteadiness on the unsteady behavior of raindrops and the WDR intensity is discussed in detail. The wind-flow field predicted with LES has been validated with wind-tunnel measurements. The mean WDR intensity values obtained using the EM model are found to be in agreement with in-situ WDR measurements. The time-resolved simulations show that the instantaneous specific catch ratio values of smaller droplets fluctuate a lot around their mean values due to higher influence of turbulence. Instantaneous specific catch ratios for the smallest raindrops are mainly dictated by local turbulent structures present in the shear layer or below the rooftop level. On the other hand, the motion of larger raindrops is mainly influenced by the larger-scale motions above the cubes. It is also shown that, running means of the specific catch ratio over a time window of 100–300 s of physical time stabilize to a constant value. Highlights: CFD simulation of unsteady wind-driven rain is performed based on LES. Influence of wind-flow unsteadiness on the behavior of raindrops is investigated. Surface wetting by large raindrops is mainly dictated by the large-scale motions. Small raindrops are mainly influenced by smaller local turbulent structures. Mean catch ratio values stabilize around a constant value after about 300 s.